Synthesis of short-chain fluorocarbon surfactant: Enhancing surface and foam performance through hydrocarbon surfactants compounding - Wenjun Zhao; Zhisheng Xu; Long Yan; Guoqing Niu (Case Studies in Thermal Engineering)
The research of short-chain fluorocarbon surfactants is crucial in effectively and environmentally extinguishing petrochemical fires. In this study, a short-chain fluorocarbon surfactant named 2H,2H-perfluorooctanoic acid sodium salt (PFH-CA) was synthesized, and then characterized its chemical structure, thermal stability, surface activity, and foam property. Subsequently, PFH-CA was compounded with hydrocarbon surfactants including sodium dodecyl sulfate (SDS), dodecyl trimethyl ammonium chloride (DTAC), and N,N-dimethyldodecylamine-N-oxid (OB-2) at different molar ratios. The surface tension, interaction parameters, and foam property of the PFH-CA/hydrocarbon surfactant compounding systems were investigated. The analysis indicates that PFH-CA exhibits excellent surface activity and thermal stability concomitant with poor foam property. Introducing SDS, DTAC, and OB-2 enhances the foam performance and reduces the consumption of PFH-CA through synergistic interactions. Especially, PFH-CA/DTAC (1:4) system possesses the strongest interactions and the best performance, with critical micelle concentration (CMC) and surface tension at CMC (γCMC) of 0.11 mmol/L and 20.90 mN/m, respectively. When concentration of PFH-CA exceeds 0.5 mmol/L, the foaming ability and foam stability stabilize at 30 cm and 90 %, respectively. The enhanced performance of PFH-CA/DTAC system is attributed to the electrostatic attraction between anionic and cationic surfactants, which facilitates the formation of micelles, subsequently leading to better surface activity and foam properties.